IMPLEMENTASI ALGORITMA PRIM SEBAGAI CREATOR JALUR PERMAINAN MAZE - Devian Ricko Hutama; R. Gunawan Santosa; Junius Karel (Jurnal Informatika, 2014)
In this modern era, computer provides more than mere a computing machine. Game is one of the advancements made, and maze is among the popular computer games. While maze is having a simple goal to exit, creating the maze itself is a challenging matter: creating a single winding and confusing path which connects one entry and one exit. This research implements the Prim Algorithm as a maze generator. User will required to enter certain size of the maze, and the system will automatically create the grids, randoming the entry and exit, and providing the necessary weight data for the grid. The Prim Algorithm will then process the weight data, rendering a maze path. This will provide a variation of maze for each game play. Results of the research shown that maze complexity is not affected by the randoming algorithm used to distribute the grid weights, but dependent to the maze size. Another result is that the number of  path walls deconstructed in an already- formed maze in order to make the correct path is carried on a certain pattern (N x N) - 1, dependent to the size of the maze (N x N).